Controllable Deadlocks in Parallel Resource-Constrained Workflows - V. A. Bashkin; N. Yu. Panfilova (Моделирование и анализ информационных систем)
We study the verification of the soundness property for workflow nets extended with resources. A workflow is sound if it terminates properly (no deadlocks and livelocks are possible). A class of resource-constrained workflow nets (RCWF-nets) is considered, where resources can be used by a process instance, but cannot be created or spent. Two sound RCWF-nets using the same set of resources can be put in parallel. This parallel composition may in some cases produce additional deadlocks. A problem of deadlock avoidance in parallel workflows is studied, some methods of deadlock search and control are presented.